Roles of Alloying Elements on the Corrosion Behavior of Amorphous W–Zr–(15–33)Cr Alloys in 1 M NaOH Solution - Kumal, Raju Ram; Bhattarai, Jagadeesh (Journal of Nepal Chemical Society, 2010)
Roles of alloy-constituting elements on the corrosion behavior of the sputter-deposited amorphous W-Zr-(15-33)Cr alloys was studied in 1 M NaOH solution open to air at 25°C using corrosion tests and open circuit potential measurements. Zirconium and chromium metals act synergistically with tungsten in enhancing the corrosion resistance of the sputterdeposited amorphous W-Zr-Cr alloys containing 15-33 at % chromium content so as to show higher corrosion resistance than those of alloy-constituting elements in 1 M NaOH solution. The corrosion rates of the amorphous W-Zr-(15-33)Cr alloys containing 9-33 at % tungsten are in the ranges of 2.0-5.0×10-3 mm.y-1 after immersion for 240 h in 1 M NaOH solution which is about two orders of magnitude lower corrosion rates lower than that of tungsten and even slightly lower than that of the zirconium metal. The simultaneous additions of zirconium and chromium metals in W-Zr-(15-33)Cr alloys are effective for ennoblement of the open circuit potential of the tungsten metal. Keywords: W-Zr-Cr alloys, corrosion resistance, immersion test, open circuit potential, 1 M NaOH. DOI: 10.3126/jncs.v25i0.3312 Journal of Nepal Chemical Society Volume 25, 2010 pp 93-100